Factors Influencing Adherence to Hazardous Waste Management Policy Frameworks among Health Workers in Private Hospitals in Nairobi County - Kenya - Chepchirchir, Constantyne; Ngoye, Ben (International Journal of Developing Country Studies, 2024)
Purpose: This study, therefore, sought to investigate the factors influencing the adherence to hazardous waste management guidelines among healthcare workers in private hospitals in Nairobi County. The specific objectives of the study included; determining the level of adherence to proper HCWM practices among health workers, identifying the individual related factors that influence adherence to proper HCWM practices among health workers, and identifying the health facility-related (institutional) factors that influence adherence to proper HCWM practices in 4 selected hospitals in Nairobi County Kenya. From the population of 900 healthcare workers from 4 levels 4 facilities, random sampling was applied to identify the 90 respondents. Methodology: Data analysis and reporting was done using appropriate quantitative methods. Findings: The findings from this study show that the level of adherence to hazardous waste management policies among healthcare workers in private level four hospitals in Nairobi County is low. Despite the high level of awareness by the health workers on the important measures of collection, segregation, treatment, transportation and disposal of waste, the level of performance on the same is low. This is greatly attributable to negligence and unfavorable attitude towards healthcare waste management practices among healthcare workers. Unique contribution to theory, policy and practice: Based on the study findings, we would recommend the improvement of hazardous waste management efficiency.